Focused Analysis of Article 29 of Indonesian Minister of Health Regulation No. 24/2022: Data Security Implementation of Electronic Medical Records at Sindangwangi Health Center, Pangandaran, West Java - Julia, Fina; Aulianto, Dwi Ridho (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Digital transformation in the healthcare sector requires the management of medical records to be conducted electronically, with emphasis on the principles of data security, including confidentiality, integrity, and availability.Objective: This research aims to analyze the management of electronic medical record data security at the Sindangwangi Health Center in accordance with Article 29 of the Indonesian Minister of Health Regulation Number 24 of 2022.Methods:  This study employs a descriptive qualitative method, collecting data through interviews and observations with informants, including one medical record officer and one registration officer, conducted from October to November 2024Results:  The management of EMR data security at Puskesmas Sindangwangi demonstrates a solid application of the CIA principles. Confidentiality is maintained through unique usernames and passwords that are updated every three months and an automatic log-out feature after inactivity. Integrity is upheld by restricting data editing to authorized personnel, with changes allowed only after one month. Availability is supported by a cloud-based system that enables real-time access. However, challenges remain, including incomplete data entry in the Emergency Department, technical disruptions such as server downtime and power outages, the use of manual systems in the cashier unit, and the absence of formal vendor agreements and disaster recovery planning.Conclusion: While the EMR system shows effective initial implementation of data security principles, improvements are needed in infrastructure, staff training, system integration, and vendor governance to ensure a more resilient and secure digital health system.